2009
DOI: 10.2140/jomms.2009.4.157
|View full text |Cite
|
Sign up to set email alerts
|

An energy-momentum conserving algorithm for nonlinear transient analysis within the framework of hybrid elements

Abstract: This work deals with the formulation and implementation of an energy-momentum conserving algorithm for conducting the nonlinear transient analysis of structures, within the framework of stress-based hybrid elements. Hybrid elements, which are based on a two-field variational formulation, are much less susceptible to locking than conventional displacement-based elements within the static framework. We show that this advantage carries over to the transient case, so that not only are the solutions obtained more a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 18 publications
(33 citation statements)
references
References 26 publications
0
33
0
Order By: Relevance
“…As mentioned in the Introduction, since each additional mode adds more stiffness, an attempt is usually made to keep the number of stress modes to a minimum, i.e., s = d −r . However, it was shown in [Jog and Motamarri 2009] that some higher-order hybrid elements that satisfy this requirement, and are free of zero-energy modes, can still give rise to instabilities in transient problems. It was shown that if the normal stresses are obtained by differentiating the displacement field, then these instabilities do not arise.…”
Section: Choice Of Stress Interpolation Functionsmentioning
confidence: 99%
See 4 more Smart Citations
“…As mentioned in the Introduction, since each additional mode adds more stiffness, an attempt is usually made to keep the number of stress modes to a minimum, i.e., s = d −r . However, it was shown in [Jog and Motamarri 2009] that some higher-order hybrid elements that satisfy this requirement, and are free of zero-energy modes, can still give rise to instabilities in transient problems. It was shown that if the normal stresses are obtained by differentiating the displacement field, then these instabilities do not arise.…”
Section: Choice Of Stress Interpolation Functionsmentioning
confidence: 99%
“…It was shown that if the normal stresses are obtained by differentiating the displacement field, then these instabilities do not arise. It is possible to interpolate the normal stresses in this manner, and such that the requirement s = d − r , and the requirement that the element matrix be free of spurious modes are still satisfied (see [Jog and Motamarri 2009] for examples). However, this involves dropping some of the lower-order terms in the shear interpolation, and this results in bad performance even on static problems.…”
Section: Choice Of Stress Interpolation Functionsmentioning
confidence: 99%
See 3 more Smart Citations